PENGARUH MILLING TERHADAP KARAKTERISTIK MOLECULARLY IMPRINTED POLYMER KARBARIL (C12H11NO2) - Suci Aprilia (Prodi Fisika FST UNJA, 2020)
Molecularly Imprinted Polymer (MIP) has been synthesized with carbaryl used as a template and forms complex bonds with Methacrylic Acid (MAA)through hydrogen bonds, followed by a cross-linking process using Ethylene Glycol Dimethacrylate (EGDMA) cross-linkers. The polymerization process begins with the thermal decomposition of Benzoyl Peroxide (BPO) as an initiator. Non-Imprinted Polymer (NIP) as a control polymer has also been synthesized using a similar procedure without using carbaryl templates. In this study, two variations of carbaryl are used, which are not milled carbamates, and carbaryl has been milled using High Energy Milling (HEM). The FTIR study was carried out to investigate the presence of carbaryl in polymers, MIP, and NIP. The spectrum shows that the concentration of carbaryl compound decreases after the extraction process. This result was also confirmed by the increase in the value of the percentage of transmittance in the MIP, especially the nano carbaryl MIP. This result is supported by the X-RD results, which showed a decrease in the size of the crystals in the carbaryl MIP from 10.07 Å while the nano carbaryl MIP was 9.16 Å.